Learning Management System: UTHM Class Hub - Muhammad Luqman Hakim; MOHD ZAKI BIN MOHD SALIKON (Applied Information Technology And Computer Science, 2025)
This research paper delves into the development of a Learning Management System (LMS) for UTHM, focusing on enhancing online education through interactive and collaborative tools. The study identifies current limitations in LMS, such as one-way learning, limited interactivity, and user-unfriendliness, particularly for diverse age groups. It emphasizes the need for a platform that not only disseminates content but also actively engages students in the learning process. The primary objectives are to design and develop a web-based LMS with real-time conferencing features and to test the system’s effectiveness. This LMS aims to transform the educational experience by fostering active student participation, critical thinking, and peer interaction. The envisioned platform includes features such as forums, an admin panel, private and public classrooms, file sharing, conferencing, and analytics. The methodology employed is the Agile development approach, particularly Scrumban, which combines the strengths of Scrum and Kanban. This approach allows for flexibility and adaptability in project development, focusing on iterative progress and responsive adjustments to changing requirements. Key findings include the successful integration of interactive elements like real-time conferencing, voting systems, private discussions, and task management. These features contribute to a more engaged learning environment, where students can collaborate, share resources, and manage their educational tasks effectively. The study concludes that the developed LMS significantly enhances collaborative learning, structured discussions, and interactive learning experiences. It suggests that future research could explore further integration of advanced technologies to elevate user engagement and learning outcomes. This research contributes to the field of educational technology by providing insights into developing more interactive and user-friendly LMS platforms, catering to the evolving needs of modern learners.